BETWEEN SYSTEMS AND VIOLENCE state-level policy targeting intimate partner violence in... immigrant and refugee lives. - Montanez, Julio; Donley, Amy M.; Reckdenwald, Amy. ([S.l.] : ROUTLEDGE, 2022)
Between Systems and Violence offers a compilation and analysis of state-level statutes targeting intimate partner violence (IPV) in immigrant and/or refugee (IMR) lives. The book analyzes such statutes' legal language via various theoretical lenses, as well as provides a discussion of implications for research, prevention, intervention, and public policy. Some IMR victim-survivors of IPV, such as those who are undocumented, may be pinned "between systems and violence" as violent partners use the immigration system as a mechanism of power and control. While protections are available for these victim-survivors, the story told about the encompassing legal landscape remains incomplete and relegated to federal law. Graduate students, as well as scholars and practitioners, will acquire an in-depth understanding of this important nexus.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Criminology; Intimate partner violence -- Government policy -- United States -- States; Intimate partner violence -- Law and legislation -- United States -- States; Immigrants -- Violence against -- United States -- States; Refugees -- Violence against -- United States -- States